Disharmonization and Blurring of Laws and Regulations Related to Termination of Employment for Persons with Disabilities Omnibus Law Era - Quraisyta, Nabilla Farah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Legal regulations related to the termination of employment for persons with disabilities, since the enactment of the copyright law there has been disharmony and blurring of norms contained in the provisions of the employment cluster. From the existence of disharmony and obscurity, it is very detrimental to people with disabilities. This research needs to be done that aims to provide input based on academic studies to overcome the disharmony and blurring of norms that occur in copyright law. Using normative juridical research methods based on a statutory approach and a conceptual approach. From this research has been found and analyzed, that it is true that there has been disharmony and blurring of norms in chapter iv of the second section of employment of the copyright law that has been contrary to disability law and contrary to the basic law. The blurring of the norm found different phrases between the two articles in the same law, namely the copyright law on the labor section, which gives rise to the interpretation of different meanings. Â